Strengthening the gig economy: Future of digital labor workforce platform post-covid-19 / Ainatul Fathiyah Abdul Rahim …[et al.] - Abdul Rahim, Ainatul Fathiyah; Yaacob, Nur Ain; Mohd Noor, Rafizah; Najid, Nurul Afzan; Zulkifli, Nursyahida (Universiti Teknologi MARA Cawangan Pahang, 2021)
COVID-19 crisis has affected most industries, companies, and businesses. This phenomenon became a major concern of the people as they start to lose their job thus pushing them to involve in the gig economy for survival. About 2.2 million gig workers in Malaysia have already registered with the Malaysian Digital Economy Corporation (MDEC). The government has allocated RM75 million to promote the gig economy and provide a social safety net for workers in the informal sector to support the aspiration of the National Agenda that is Sustainable Development Goals. The prospect of the gig economy has transformed the traditional workforce platform into a new platform that has a very high potential as it can create job opportunities, capacity enhancement, and expand a new field of the labor force in several sectors. The growth of the gig economy, typified by online platforms and isolated independent workers, poses fundamental challenges to traditional models for regulating work and setting minimum standards. This causes the government and employers to reshape the best way to approach employment in the future. Hence, this research aims; i.to examine current practices of the gig economy, ii. to analyze the existing digital labor policy initiatives for the digital labor workforce, iii. to recommend a framework of digital labor workforce platform to strengthen the gig economy as to create a decent working condition framework of the digital labor workforce soon will benefit citizens and the country. Hence, this research can fulfil Goal No 8 of Sustainable Development Goals that are promoting sustained, inclusive, and sustainable economic growth, full and productive employment, and decent work for all.